2021
DOI: 10.1093/nar/gkab683
|View full text |Cite
|
Sign up to set email alerts
|

A cascade of transcriptional repression determines sexual commitment and development in Plasmodium falciparum

Abstract: Gametocytogenesis, the process by which malaria parasites produce sexual forms that can infect mosquitoes, is essential for the transmission of malaria. A transcriptional switch of the pfap2-g gene triggers sexual commitment, but how the complex multi-step process is precisely programed remains largely unknown. Here, by systematic functional screening of a panel of ApiAP2 transcription factors, we identify six new ApiAP2 members associated with gametocytogenesis in Plasmodium falciparum. Among these, PfAP2-G5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 47 publications
2
71
0
Order By: Relevance
“…Elucidation of the role of essential P. falciparum ApiAP2 proteins in the IDC is challenging due to the inability to knockout asexual blood stage essential genes from the parasite's haploid genome. Previous attempts to knockout AP2-EXP [27][28][29]33 failed to produce parasite lines in which the AP2 domain coding sequence was disrupted. We similarly did not recover transgenic parasites after attempting to completely disrupt the coding sequence for AP2-EXP using the targeted gene disruption (pSLI-TGD) system 51 in three independent attempts, suggesting that AP2-EXP is essential for the IDC (not shown).…”
Section: Plasmodium Parasitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Elucidation of the role of essential P. falciparum ApiAP2 proteins in the IDC is challenging due to the inability to knockout asexual blood stage essential genes from the parasite's haploid genome. Previous attempts to knockout AP2-EXP [27][28][29]33 failed to produce parasite lines in which the AP2 domain coding sequence was disrupted. We similarly did not recover transgenic parasites after attempting to completely disrupt the coding sequence for AP2-EXP using the targeted gene disruption (pSLI-TGD) system 51 in three independent attempts, suggesting that AP2-EXP is essential for the IDC (not shown).…”
Section: Plasmodium Parasitesmentioning
confidence: 99%
“…Their plant-like origin distinguishes them from all other known transcription factors in humans or mosquitoes 20 . Over half of the ApiAP2 proteins are predicted to be essential for the IDC in P. falciparum based on a random mutagenesis screen 26 , and in targeted knockout screens only 11/23 ApiAP2 coding sequence disruptions attempted were successful [27][28][29] . In the rodent malaria model species P. berghei 30 and P. yoelii 31 , 11 ApiAP2 proteins have developmental lethal phenotypes in the sexual blood or mosquito stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of AP2-G promotes the transcription of early gametocyte genes, which leads to gametocyte commitment and formation [4][5][6]. In a recent study, it was shown that another transcription factor AP2-G5 is essential for gametocyte maturation through the down-regulation of AP2-G and a set of genes activated by AP2-G prior to gametocyte development [7]. Other transcription factors such as AP2-FG and AP2-O3 have been shown to regulate gene expression in female gametocytes [8,9] and ookinete development by AP2-O family [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…According to latest research, scientists have successfully knocked out 11 ApiAP2 transcription factors in P. falciparum and have gained a preliminary insight into their functions ( Shang et al, 2021 ; Singh et al, 2021 ). PfAP2-G is recognized as the master positive regulator of sexual conversion between gametocyte commitment and development, while PfAP2-G5 and PfAP2-G2 work together as transcriptional repressors ( Kafsack et al, 2014 ; Sinha et al, 2014 ; Poran et al, 2017 ; Xu et al, 2020 ; Shang et al, 2021 ; Singh et al, 2021 ). Another ApiAP2 family member, which is named PfAP2-I, has been reported to regulate the process of invasion ( Santos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%